A Study On The Damage To A Mine Drift Caused By Blast Welding - Jang, Hyong Doo; Han, K.; Kim, W.; Yang, H.; Jang, M. (2010)
Explosive welding is planned in an abandon drift which is approximately 10m radius and 9m height. According to the plan the amount of explosive, ANFO will be up to 1000kg per stage. Before the explosive welding experiment, the environmental analysis especially about the air-blast overpressure should be concerned because that the explosive welding is methodologically similar to open pit blasting. The air-blast overpressure could give damages to nearby structures and cause human annoyance. Normally in tunnels and drifts in a mine, a damping ratio of the overpressure is lower than open space because that reflected pressures are easily get together in a sealed condition. In this study we investigate a safety of nearby pillar and upper wall from the overpressure in a drift using the overpressure estimate equations from CONWEP and DDESB. As the results, strength of composed limestone in the drift is higher than the overpressure in a common distance. However the overpressure can cause a weakness of nearby pillar and roof in a drift which contain narrow parallel joints.